2013
DOI: 10.21608/eajbsc.2013.16114
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Inhibition (AChE) in Brain of Oreochromis mossambicus due to Pesticidal Pollution of Herbicide “Pursuit”

Abstract: In the present investigation, the effect of three sublethal concentrations of Pursuit, that is, 63.7 ppm, 85 ppm, and 127.5 ppm in Oreochromis mossambicus was studied. Pursuit inhibited acetyl cholinesterase in the brain of Oreochromis mossambicus by increasing the K m and V max , thereby acting as a mixed inhibitor. The assay of brain AChE is thus useful for monitoring pesticide toxicity of fish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
1
1
0
1
Order By: Relevance
“…Analyzing the biochemical aspect, IMZT is also capable of inducing alterations in AChE activity in L. latinasus adults. In this sense, our results corroborate the same effects reported in sh by Pasha and Singh (2005), Moraes et al (2011) and Pasha (2013), where IMZT alters the cholinergic system of local aquatic vertebrates. Oxidative stress refers to the imbalance due to excess ROS or oxidants over the cell's ability to carry out an effective antioxidant response.…”
Section: Discussionsupporting
confidence: 91%
“…Analyzing the biochemical aspect, IMZT is also capable of inducing alterations in AChE activity in L. latinasus adults. In this sense, our results corroborate the same effects reported in sh by Pasha and Singh (2005), Moraes et al (2011) and Pasha (2013), where IMZT alters the cholinergic system of local aquatic vertebrates. Oxidative stress refers to the imbalance due to excess ROS or oxidants over the cell's ability to carry out an effective antioxidant response.…”
Section: Discussionsupporting
confidence: 91%
“…No obstante, se reportó que la exposición a IMZT como principio activo y en formulados comerciales, produce estrés oxidativo en células hepáticas de Cyprinus carpio (carpa común) al evaluar distintos parámetros bioquímicos como la respuesta de las enzimas de estrés oxidativo y enzimas colinesterasas (Moraes y col. 2011). Estos efectos también fueron reportados para O. mossambicus (tilapia de Mozambique) luego de la exposición a formulados comerciales (Pasha y Singh 2005, Pasha 2013. De cualquier manera, hasta el momento para otros vertebrados acuáticos como los anfibios, no se tiene registros sobre los posibles efectos adversos de IMZT.…”
Section: Herbicida Imazetapir: Características Toxicidad Y Genotoxicunclassified
“…Furthermore, analyzing in aquatic vertebrates, Moraes et al (2011) reported alterations on enzymes related to oxidative stress after 0.0148 mg/L exposure to both the active ingredient IMZT and to the IMZT-based commercial herbicide formulation Only® in hepatic tissues of the sh Cyprinus carpio. In addition, inhibition of acetylcholinesterase (AChE) was informed after exposure to commercial formulations of IMZT in the Mozambique tilapia (Pasha and Singh, 2005;Pasha, 2013). Recently, in other aquatic vertebrates, our research group has demonstrated the toxicological effects at genetic, biochemical and individual level in anurans such as Boana pulchella and Leptodactylus latinasus exposed to IMZT at their larval phase (Pérez-Iglesias et al, 2015;2017;2020).…”
Section: Introductionmentioning
confidence: 99%